Analisis Dinamika Model Penyakit Toksoplasmosis pada Populasi Kucing dan Manusia - Rusdiani, Riza; Kusnanto, Ali; Sianturi, Paian (Jurnal Matematika; Vol 11 No 2 (2021)DO - 10.24843/JMAT.2021.v11.i02.p138, 2022)
Abstract : Toxoplasmosis is a disease that is identical to cats. This disease is caused by the parasite Toxoplasma gondii. In this study, a mathematical model of the spread of toxoplasmosis was reviewed with various population size. In this study ,   model  construct ion, fixed point analysis and  parameter sensitivity  analysis were  carried out .  From the sensitivity analysis , it is shown that the cat transmission rate from a susceptible cat population to an infected cat population (horizontal transmission rate) and the probability of a susceptible cat born from an infected cat (vertical transmission  rate) are found as sensitive parameters on  production number (  Decreasing the horizontal transmission  rate   and an  increase value of the vertical transmission rate can reduce the value of   A decrease in the value of , results in a disease-free state will be achieved more quickly so that the disease is under control.